Headache Associated with Chiari Malformation Type One - Seddeg, Yasser; Awad, Ali; Osman, Haytham (My University, 2020)
Background: Patients with chiari malformation type one ( CM -1 ) headache may be mistaken by chronic migraines or other causes of headache, so analysis of headache related to CM-1 is corner stone in early diagnosis of the disease. Objective: The purpose of this study was to assess the frequency and clinical characteristics of headache in the patients with CM-1 to help primary care clinicians better understand the relationship between an individual's presenting symptoms of CM 1, so aiding for early diagnosis and early management and for better outcome. Methods: This was prospective observational analytical study carried out in Khartoum state hospitals that provide neurosurgical services, (NCNS, Neurospine Center-Ribat Teaching Hospital, Military Hospital, and Omdurman Teaching Hospital) from February 2018- September 2019. Study was included 18 adult males and females of different ages diagnosed with Chiari MF -1 who undergoing decompressive surgery. Symptomatic patients diagnosed with Chiari MF -1Patients with no history of neurological illnesses or history of cranial surgery were included. Patients with history of any neurological diseases such as multiple sclerosis and with other causes of headache were excluded from the study. Evaluation and full analysis of headache were registered including type of headache, site, duration headache, time lasting, radiation of pain, severity using headache scale, associated ocular and visual symptoms. Results: This study included 18 patients diagnosed with chiari 1 malformation and suffering from headache related to chiari 1 malformation. Full analysis of the headache was obtained. The headache was mostly in the back of the head (n=17/18 , 94.4%) and only in (n=1/18, 5.6%), the headache was in the sides or front of the head. In 12 patients (n=12/18 , 66.7%) headache worsen by bending forward. And in 6 patients (n=6/18 , 33.3%) worsen by cough. Regarding the type of headache, mostly pressure in nature (n=17/18 , 94.4%) and it was rarely throbbing in nature(n=1/18, 5.6%),. All patients were asked to evaluate their headache in headache scale from 1 to 10 (10 more severe). The scale ranged between 5 and 9 with mean 6.88. headache could be long or short lasting (from hours to days).Eye symptoms included blurring of vision complained by 9 patients(n=9/18, 50%), light sensitivity in 5 patients ((n=5/18, 27.8%), and 6 patients (n=6/18 , 33.3%) there were no eye symptoms. Neck pain was a dominant symptom seen in 17 patients (n=17/18, 94.4%) , and back pain in 18 patients (n=18/18 , 100%) . headache subsided after decompression surgery in all patients included in this study. Conclusion: Knowledge and understanding the CM-1 headache characters are important for early diagnosis and early treatment of the disease.
Keywords: Chiari malformation; CM-1; Headache; occipital headache; neck pain